2022
DOI: 10.1002/cae.22545
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implementing project‐based assignment (PBA) in CDIO framework for computer numerical control application course

Abstract: Over the past decades, the development of engineering skills among students has been drastically reduced in Indian education. The students need to develop not only knowledge but also the necessary skills to survive in fastgrowing technology. Particularly in industry-related automation courses, the fourth industrial revolution (Industry 4.0) adds to the necessity of building engineering skills at a higher level. It is well observed from various educational studies that engineering skills with higher cognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…, where Vac(x, y) is covariance between u and v and δ u and δ v are standard deviations [10]. According to the correlation table, the students in the remote laboratory batch for 2020-2021 have a greater correlation that is almost 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, where Vac(x, y) is covariance between u and v and δ u and δ v are standard deviations [10]. According to the correlation table, the students in the remote laboratory batch for 2020-2021 have a greater correlation that is almost 1.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes of the virtual and remote lab exams that students enrolled in the online curricula for 2019–2020 and 2020–2021 are displayed in Table 6. The coefficient of correlation using Karl Pearson's analysis is ρ=italicVac(u,v)δuδv $\rho =\frac{{Vac}(u,v)}{{\delta }_{u}{\delta }_{v}}$, where Vac( x , y ) is covariance between u and v and δu ${\delta }_{u}$ and δv ${\delta }_{v}$ are standard deviations [10]. According to the correlation table, the students in the remote laboratory batch for 2020–2021 have a greater correlation that is almost 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, CDIO programs exhibit considerable potential in engineering education [30]. However, it is imperative to acknowledge and address certain crucial factors that warrant further investigation in future research endeavors.…”
Section: Difficulties and Prospects Of Engineering Education Cdio Pro...mentioning
confidence: 99%
“…CDIO has been applied in various research areas, such as engineering education (Martin & Wackerlin, 2016), geology (De León, 2014)、mass communication (Tangkijviwat et al, 2018), and architectural education (Nyka et al, 2020). In addition, the CDIO teaching model can be integrated into learning activities to enhance high-order thinking, Julius Fusic et al (2022) designed an experiment to verify whether the CDIO model can achieve analytical and evaluation cognitive levels in mechatronics engineering learning activities. The results showed that students using the CDIO framework are better than other students at acquiring higher-order thinking skills.…”
mentioning
confidence: 99%